The Soviet Defence Industry Complex from Stalin to Krushchev
XVIII, 283 p.
Keywords: The huge complex of Soviet institutions and enterprises specialised in military production powerfully influenced the course of the twentieth century through resistance to imperial Japan, the defeat of Nazi Germany, and nuclear stalemate with America in the Cold War. Based on collaborative research by Russian and British scholars in the hitherto secret archives of the Soviet government, party, and armed forces, this book is a pioneering investigation of the economic dynamics and social and political significance of Soviet defence.